2023
DOI: 10.1088/1475-7516/2023/03/011
|View full text |Cite
|
Sign up to set email alerts
|

Halo-independent bounds on the non-relativistic effective theory of WIMP-nucleon scattering from direct detection and neutrino observations

Abstract: We combine experimental constraints from direct detection searches and from neutrino telescopes looking for WIMP annihilations in the Sun to derive halo-independent bounds on each of the 28 WIMP-proton and WIMP-neutron couplings of the effective non-relativistic Hamiltonian that drives the scattering process off nuclei of a WIMP of spin 1/2. The method assumes that the velocity distribution is normalized to one and homogeneous at the the solar system scale, as well as equilibrium between WIMP capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…As far as the quantitative bound on the coupling is concerned, in ref. [47] it was shown that for the case of elastic scattering (δ = 0) increasing u max by a factor of ten (i.e. to a value that largely exceeds the expectations for the escape speed in our Galaxy) weakens the single-stream bound by at most a factor of two, due to the suppression of the form factor in the WIMP-nucleus scattering process at large nuclear recoil energies.…”
Section: Jcap11(2023)077mentioning
confidence: 59%
See 4 more Smart Citations
“…As far as the quantitative bound on the coupling is concerned, in ref. [47] it was shown that for the case of elastic scattering (δ = 0) increasing u max by a factor of ten (i.e. to a value that largely exceeds the expectations for the escape speed in our Galaxy) weakens the single-stream bound by at most a factor of two, due to the suppression of the form factor in the WIMP-nucleus scattering process at large nuclear recoil energies.…”
Section: Jcap11(2023)077mentioning
confidence: 59%
“…where c NT max (u) and c DD max (u) correspond to c max (u) for the NT and the DD experiments, respectively, and ũ denotes the speed where c NT max and c DD max intersect at a finite value c, i.e., c NT max (ũ) = c DD max (ũ) = c. In this case, using eq. (4.7) it can be shown that (see [38] and [47] for details) the halo-independent bound on the coupling is:…”
Section: Jcap11(2023)077 4 Halo-independent Bounds With the Single-st...mentioning
confidence: 99%
See 3 more Smart Citations